Cognitive learning versus practical “hands-on” training for acquisition of laparoscopic surgical skills: an optimal combination study - Cizmic, Amila; Schwabe, Nils; Häberle, Frida; Killat, David; Giannou, Anastasios D.; Preukschas, Anas; Nießen, Anna; Pianka, Frank; Billmann, Franck; Mehrabi, Arianeb; Müller, Beat P.; Hackert, Thilo; et al. (Surgical endoscopy and other interventional techniques, 2025)
Most minimally invasive surgery (MIS) training curricula involve practical training (PT) and cognitive learning (CL) to different extents. It has been proven that acquiring and training specific skills through CL can improve MIS skills. This study aimed to discover the most efficient combination of these two approaches and examine their effects on acquiring MIS skills in novices.
Online veröffentlicht: 27. März 2025
Gesehen am 15.10.2025